2010
DOI: 10.1620/tjem.222.155
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Nerve Regulation Is Essential for the Increase in Gastric Motility in Response to Mild Exercise

Abstract: It has been shown that mild to moderate exercise can accelerate gastric emptying in humans. However, understanding of the underlying mechanism is hampered by the lack of appropriate animal models. To investigate the effects of mild exercise on gastric motility, we developed an animal model, in which strain gauge transducers were surgically planted on the antral surfaces of female Sprague-Dawley rats. We continuously recorded the contractions of gastric circular muscle in unrestrained conscious rats, divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The relative dominance of sympathetic/parasympathetic activity is also influenced by exercise conditions [91]. During moderate intensity exercise, the vagal nerve appears to have a critical role in accelerating GE [30]. In addition, more powerful and stable gastric myoelectrical activity following moderate exercise could contribute to a faster GE [86,92].…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative dominance of sympathetic/parasympathetic activity is also influenced by exercise conditions [91]. During moderate intensity exercise, the vagal nerve appears to have a critical role in accelerating GE [30]. In addition, more powerful and stable gastric myoelectrical activity following moderate exercise could contribute to a faster GE [86,92].…”
Section: Mechanismsmentioning
confidence: 99%
“…In contrast, peptide YY and glucagon-like peptide 1 act as satiety signals and to inhibit GE [28]. In addition to hormonal influences, mechanical or neural factors such as the relative dominance of parasympathetic or sympathetic tone may contribute to variable GE responses to exercise [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulating gastric motility agents also enhances gastric emptying [19-21]. On the other hand, higher concentrations SAWF may have a beneficial effect on symptoms associated with rapid gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is thought to result from stimulating the VN, as the effect from exercise is abolished after vagotomy [52]. Studies have shown that cardiac vagal tone as assessed with HRV is increased in athletes compared to sedentary controls [53].…”
Section: Aerobicmentioning
confidence: 99%